TPH gene polymorphisms are associated with disease perception and quality of life in women with irritable bowel syndrome - Jun, Sang-Eun; Kohen, Ruth; Cain, Kevin C; Jarrett, Monica E; Heitkemper, Margaret M (Biological research for nursing, 2014)
The aims of this exploratory study were to examine whether tryptophan hydroxylase (TPH) gene polymorphisms are associated with psychosocial factors in women with irritable bowel syndrome (IBS). TPH is the rate-limiting enzyme in the biosynthesis of serotonin and has two isoforms, TPH1 and TPH2. Four single nucleotide polymorphisms (SNPs) in the TPH1 gene and one SNP in the TPH2 gene were selected based on previous studies investigating associations between these SNPs and psychiatric or behavioral disorders. One hundred ninety-nine Caucasian women with IBS were included. Results of univariate analysis showed no association between TPH1and TPH2 gene SNPs and current level of psychological distress or psychiatric illness. However, TPH1 gene SNPs were associated with IBS-related cognitions (rs4537731 and rs21105) and quality of life (rs684302 and rs1800532), in particular the mental health and energy subscales. These associations were independent of the subjects' levels of gastrointestinal symptoms. These results suggest that patients' perception of their illness, and of the impact it has on their lives, may be subject to genetic influences, in this case sequence variants in TPH1. However, caution should be used in interpreting these results given the large number of hypothesis tests performed in this exploratory hypothesis-generating study, and the results should be considered tentative until confirmed in an independent sample.